Gene expression profiling of Ctr9-regulated transcriptome in ERα-positive breast cancer - Hao Zeng (Genomics Data, 2016)
Ctr9, the key scaffold subunit in human RNA polymerase II associated factor complex (PAFc), has diverse functions in cells and has been implicated in human diseases. Recently, our study found that loss of Ctr9 led to apparent morphological change, decrease of proliferation, and reduced colony formation in ERα+ breast cancer cells. Moreover, Ctr9 and ERα show positive correlation at protein levels and the high levels of Ctr9 are associated with poor survival among all women with ERα+ breast cancers, and specifically among those treated with tamoxifen. To gain a molecular understanding of the role of Ctr9 in promoting ERα+ breast cancer, we performed a microarray gene expression profiling of Ctr9-regulated transcriptome. Here we provide the experimental details and analysis of the microarray data, which have been deposited into Gene Expression Omnibus (GEO): GSE73388. Keywords: Ctr9, Breast cancer, Microarrays, Transcriptional profiling